The role of socially contextual mobile technologies in enabling the digital inclusion of female informal economy traders in Africa - Mbali Ndandani (Graduate School of Business (GSB), 2024)
Purpose: There has been research conducted regarding the digital inclusion of informal economy traders, however, there has been less scholarly work detailing the lived experiences of informal economy traders, alongside the lived experiences of technology startups building solutions for the informal economy. This research sought to contribute to this nascent interdisciplinary area of study by deepening understanding of the intersection between 1) the informal economy and female entrepreneurship, 2) the sociological considerations of digital inclusion for female informal entrepreneurs, and 3) the context of mobile technology startups building solutions for the informal economy. Design/methodology/approach: This study used the case study method, emerging with two case studies- the first being the technology startup entrepreneurs and the second being a case for female informal economy entrepreneurs. Data was collected via in depth semi structured interviews for both case studies. Findings: The findings of this study show that by connecting the lived experiences of female informal entrepreneurs and surfacing the lived experiences of the technology startup entrepreneurs building solutions for digital inclusion in the informal economy in Africa, a co-learning and co-creative relationship can be nourished between them. Research implications: This research contributes an interdisciplinary conceptual framework by describing how the fields of the informal economy, female entrepreneurship, digital inclusion and mobile technology innovation in emerging economies can be connected. This interconnectedness can enable technology startup entrepreneurs and female informal economy entrepreneurs to journey towards and nourish a co-creative relationship that influences and translates to the systemic lens of digital inclusion in the informal economy. Practical implications: The conceptual framework proposed in this research would be of value to practitioners and startups developing solutions for the informal economy, by becoming, not a set of rigid rules, but a reference point, and guideline that may allow them to engage the system of informal entrepreneurs and their own system in deeper, more meaningful ways towards the goals of co-learning and co-creation of innovative solutions